The effect of albendazole toward anemia in children with soil-transmitted helminths infection in a remote and endemic area (Medical Journal of Indonesia, 2018)
Background: Soil-transmitted helminths (STH) infections lead to nutritional disorder and anemia among children. Albendazole 400 mg is used to control STH, although it has a low cure rate for Trichuris trichiura. The effectiveness of albendazole could be increased by giving a dose of 400 mg for 3 consecutive days. The aim of the study was to investigate the effectiveness of the triple-dose albendazole 400 mg course in decreasing STH and anemia prevalence.Methods: This study used an experimental comparative design conducted in July 2016 and January 2017 in Perobatang Village, Southwest Sumba, Indonesia. Children aged 1–15 years were asked to collect fecal samples to be examined using a Kato-Katz method. Hemoglobin level (Hb) was tested using a rapid test diagnostic strip. STH positive subjects were given 400 mg of albendazole for 3 days witnessed by the researchers. Six months after, the stool samples and Hb levels were re-examined (post-test).Results: From the 156 subjects examined (pretest), the prevalence of Ascaris lumbricoides, Trichuris trichiura, and hookworm were 65.4%, 55.8%, and 15.4%, respectively, and the prevalence of anemia was 71.2%. On post-test, the prevalence of A. lumbricoides, T. trichiura, and hookworm decreased to 8.3%, 12.8%, and 0%, respectively, and the prevalence of anemia decreased to 25%. There was a significant difference in the prevalence of STH infection and anemia before and after the administration of triple-dose albendazole (p=0.001).Conclusion: The triple-dose albendazole is effective in reducing the prevalence of STH and anemia in children with STH infection.